Limb Muscle Reinnervation with the Nerve-Muscle-Endplate Grafting Technique: An Anatomical Feasibility Study - Liancai Mu; Jingming Chen; Jing Li; Stanislaw Sobotka; Themba Nyirenda (Neurology Research International)
Background. Peroneal nerve injuries results in tibialis anterior (TA) muscle paralysis. TA paralysis could cause “foot drop,” a disabling condition that can make walking difficult. As current treatment methods result in poor functional recovery, novel treatment approaches need to be studied. The aim of this study was to explore anatomical feasibility of limb reinnervation with our recently developed nerve-muscle-endplate grafting (NMEG) in the native motor zone (NMZ). Methods. As the NMEG-NMZ technique involves in nerves and motor endplates (MEPs), the nerve supply patterns and locations of the MEP bands within the gastrocnemius (GM) and TA muscles of rats were investigated using Sihler’s stain and whole-mount acetylcholinesterase (AChE) staining, respectively. Five adult rats underwent TA nerve transaction. The denervated TA was reinnervated by transferring an NMEG pedicle from the ipsilateral lateral GM. At the end of a 3-month recovery period, maximal muscle force was measured to document functional recovery. Results. The results showed that the TA was innervated by the deep peroneal nerve. A single MEP band was located obliquely in the middle of the TA. The GM was composed of two neuromuscular compartments, lateral (GM-l) and medial (GM-m), each of which was innervated by a separate nerve branch derived from the tibial nerve and had a vertically positioned MEP band. The locations of MEP bands in the GM and TA muscles and nerve supply patterns demonstrated that an NMEG pedicle can be harvested from the GM-l and implanted into the NMZ within the TA muscle. The NMEG-NMZ pilot study showed that this technique resulted in optimal muscle force recovery. Conclusion. NMEG-NMZ surgery is feasible for limb reinnervation. Specifically, the denervated TA caused by peroneal nerve injuries can be reinnervated with a NMEG from the GM-l.